Phenotypic variability and the gender paradox in the R363C variant of Fabry disease - Alison C. Leslie; Jeanine Jarnes; Alia Ahmed; Sofia Shrestha; Jeffrey Wang; Chester B. Whitley; Nishitha R. Pillai (JIMD Reports)
Abstract Fabry disease is an X‐linked lysosomal disease caused by variants in the GLA gene. Although Fabry disease is X‐linked, GLA gene variants in females can exhibit a wide range of symptoms, challenging the traditional view of Fabry as an X‐linked recessive disease. A family is presented here with a 36‐year‐old female who is symptomatic with chronic kidney disease and her oligosymptomatic 70‐year‐old father, both of whom have a heterozygous and hemizygous GLA pathogenic variant, respectively, c.1087C>T (p.R363C). Interestingly, the proband's Lyso‐GL‐3 levels were lower than her father's despite her more severe clinical presentation. The discordance between clinical severity and Lyso‐GL‐3 levels, particularly in the context of migalastat therapy, raises questions about the appropriate interpretation and use of this biomarker. The earlier and more severe symptom onset in the female proband suggests the potential role of genetic modifiers or other factors influencing disease expression. This report underscores the complexity of Fabry disease phenotypes and the limitations of current biomarkers in predicting disease severity, particularly in females. The observed paradox between clinical symptoms and biomarker levels suggests the need for a deeper understanding of the underlying mechanisms driving phenotypic variability in Fabry disease.